Experimental and correlated liquid–liquid equilibrium data for (water + 1, 6-hexanediol + 1-butanol or 2-methyl-1-propanol). (January 2021) - Yang, Xingchuan; Chen, Xiangmeng; Cao, Chunmei; Xu, Li; Liu, Guoji
Highlights: Solubility and LLE data for water + 1, 6-hexanediol + 1-butanol or 2-methyl-1-propanol were measured. Distribution coefficients and separation factors were calculated. 2-methyl-1-propanol is a better choice for extraction of 1, 6-hexanediol from water. The experimental data were correlated by NRTL and UNIQUAC models. Abstract: Solubility and liquid–liquid equilibria data for ternary systems for (water + 1, 6-hexanediol + 1-butanol/2-methyl-1-propanol) were obtained at (293.15–323.15) K under atmospheric pressure. The LLE data were determined using a double-jacketed glass vessel, and the solubility curves were acquired by the cloud-point method. The distribution coefficient and separation factors were calculated and the reliability of experimental data was assessed by the Othmer–Tobias equation and Hand equation. The measured LLE data were fitted by NRTL and UNIQUAC models and binary parameters were obtained by using of Aspen Plus software. The calculated root-mean-square deviation values show that the calculated results from models showed good agreement with experimental data.